Bullous pemphigoid with hyperkeratosis and palmoplantar keratoderma: Three cases. Issue 9 (14th July 2018) - Fania, Luca; Didona, Dario; Pacifico, Valeria; Mariotti, Feliciana; De Luca, Naomi; Abeni, Damiano; Mazzanti, Cinzia; Di Zenzo, Giovanni; Didona, Biagio
Abstract: The clinical features of bullous pemphigoid are extremely polymorphous. Several atypical forms of bullous pemphigoid have been described, and the diagnosis critically relies on immunopathological findings. We describe three bullous pemphigoid patients characterized by palmoplantar keratoderma, diffused hyperkeratotic cutaneous lesions and extremely high levels of immunoglobulin E serum. The diagnosis of bullous pemphigoid should be taken into account in patients presenting diffused hyperkeratotic cutaneous lesions and palmoplantar keratoderma, even in the absence of blisters. Alteration of the keratinization process, that could occur in patients with genetic mutations in desmosomal and hemidesmosomal genes, may also be due to circulating autoantibodies against hemidesmosomal proteins in these bullous pemphigoid patients.